An Examination of the Psychological Processes Behind Effective Piano Practice - WANG KELI (Pacific International Journal, 2024)
This study explores interplay between psychological processes and piano practice, unveiling how cognitive theories, mindfulness, flow state, emotional engagement, and performance psychology collectively shape the pianist’s journey. By examining the foundation of deliberate practice driven by focused attention, this study uncovers its role in skill acquisition. Introducing mindfulness practices enriches piano practice through heightened present-moment awareness, fostering focused engagement and emotional regulation. The pursuit of flow state, characterized by the alignment of challenge and skill, leads to immersive and productive practice sessions. Moving to interpretation, the study explores how psychological factors infuse emotion and authenticity into performances. Mindset, emotional intelligence, and personal narratives emerge as pivotal in conveying a piece’s intended narrative. Performance psychology then comes into play, influencing psychological states during performances and strategies for managing anxiety. Overall, the implications for piano pedagogy emphasize nurturing mindful learning environments, fostering flow experiences, and guiding emotional expression, thus embracing a holistic approach. This study underscores the transformative impact of psychology in shaping the trajectory from novice pianist to expressive artist, unraveling the profound interrelation between the mind and the art of piano playing.